EFFECTIVENESS OF PROGRESSIVE MUSCLE RELAXATION (PMR) WITH MOZART’S CLASSIC MUSIC ON BLOOD PRESSURE TO PATIENT CHRONIC KIDNEY DISEASE (CKD) WITH INTRADIALYTIC HYPERTENSION (IDH) - Nirmala Nirmala; Santi Herlina (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2025)
Chronic kidney disease (CKD) can develop into end stage renal disease (ESRD), requiring hemodialysis therapy. However, this can cause complications such as intradialytic hypertension (IDH), defined as a pre-HD blood pressure >140/90 mmHg or a post-HD blood pressure > 130/80 mmHg. Therefore, the combination of PMR with mozart classical music is recommended. This study aims to analyze the effectiveness of this combined therapy on blood pressure. The research design is quasi experimental using descriptive tests, paired t tests and independent t tests. With a purposive sampling technique, a sample of 38 respondents was divided into intervention and control groups in the hemodialysis unit of RSUD Tarakan. The results showed a significant effect on SBP (p value <0.001) and DBP (p value <0.001) in the intervention group, SBP (p value <0.001) and DBP (p-value = 0.003) in the control group, and significant differences in post-dialysis SBP (p-value = 0.001) and DBP (p value <0.001) between the two groups. In the intervention group, there was a decrease in SBP and DBP, whereas in the control group, there was an increase in SBP and DBP. Therefore, this combined therapy can be a complementary treatment for CKD patients with IDH to stabilize blood pressure, especially during intradialysis.